Analysis Of Motor Chiller Safety System In Store Building - Ismail, Ismail (Sean Institute, 2022)
Security of the chiller is very necessary, especially to protect the motor from interference so that it can also protect the chiller from damage that occurs, in addition to protecting the surrounding environment and living things (humans). Disturbances that arise in the chiller can be caused by current and voltage, unstable loads on the motor or from its environment; This can cause damage to the motor, fire and death. The safety equipment used in the chiller motor safety system can be in the form of circuit breakers (MCCB and ELCB) or Phase Failure Relay (Motor Saver). MCCB is used as short circuit, overload and overcurrent protection; ELCB for leakage current; while the Motor Saver is used for safety of less/over voltage, asymmetrical voltage.